Gender-specific associations between apolipoprotein A1 and arterial stiffness in patients with nonalcoholic fatty liver disease - Sun,Xulong; Chen,Ruifang; Yan,Guangyu; Chen,Zhiheng; Yuan,Hong; Huang,Wei; Lu,Yao (PeerJ, 2020)
Background Lipid metabolism factors may play an important role in the progression of nonalcoholic fatty liver disease (NAFLD) and its related cardiovascular dysfunctions. The study aims to assess whether Apolipoprotein A-1 (ApoA1) was associated with vascular stiffness in NAFLD patients. Methods From 2012 to 2013, we included 2,295 non-alcohol users with fatty liver disease (1,306 male patients) and completely excluded subjects who drank any alcohol ever to eliminate the effect of alcohol intake. The serum ApoA1 levels and the brachial-ankle pulse wave velocity (baPWV) were measured. Results The baPWV in men was much higher than in female patients (1,412.79 cm/s vs. 1,358.69 cm/s, P < 0.001). ApoA1 level was positively associated with baPWV odd ratio (OR), 4.18; 95% confidence interval (CI) [1.16–15.1], P < 0.05) in patients with AST/ALT < 1 and (OR, 4.70; 95% CI [1.36–16.23], P < 0.05) in patients with AST/ALT ≥ 1 respectively. Only arterial stiffness in men was associated with ApoA1 (OR, 3.96; 95% CI [1.29–12.30], P < 0.05) in logistics regression models adjusted for age, gender, body mass index, education attainment, physical activity, smoking, history of hypertension and high-density lipoprotein. The relationship between ApoA1 and baPWV in male NAFLD patients remained significant (confidence, 156.42; 95% CI [49.34–263.50], P < 0.05) in the fully adjusted linear regression model. Conclusion The serum ApoA1 was associated with arterial stiffness in male NAFLD patients. Increased ApoA1 level should be considered as an independent risk factor for arterial stiffness in male NAFLD patients, suggesting that NAFLD may alter arterial stiffness by “ApoA1-related” mechanism in men.
Keywords: Non-alcoholic fatty liver disease; Arterial stiffness; ApoA1; Gender